A trial of e-simulation of sudden patient deterioration (FIRST2ACT WEB™) on student learning. (October 2015) - Bogossian, Fiona E.; Cooper, Simon J.; Cant, Robyn; Porter, Joanne; Forbes, Helen; ,
Summary: Background: High-fidelity simulation pedagogy is of increasing importance in health professional education; however, face-to-face simulation programs are resource intensive and impractical to implement across large numbers of students. Objectives: To investigate undergraduate nursing students' theoretical and applied learning in response to the e-simulation program—FIRST2ACT WEBTM, and explore predictors of virtual clinical performance. Design and setting: Multi-center trial of FIRST2ACT WEBTM accessible to students in five Australian universities and colleges, across 8 campuses. Participants: A population of 489 final-year nursing students in programs of study leading to license to practice. Methods: Participants proceeded through three phases: (i) pre-simulation—briefing and assessment of clinical knowledge and experience; (ii) e-simulation—three interactive e-simulation clinical scenarios which included video recordings of patients with deteriorating conditions, interactive clinical tasks, pop up responses to tasks, and timed performance; and (iii) post-simulation feedback and evaluation. Descriptive statistics were followed by bivariate analysis to detect any associations, which were further tested using standard regression analysis. Results: Of 409 students who commenced the program (83% response rate), 367 undergraduate nursing students completed the web-based program in its entirety, yielding a completion rate of 89.7%; 38.1% of students achieved passing clinical performance across three scenarios, and the proportion achieving passing clinical knowledge increased from 78.15% pre-simulation to 91.6% post-simulation. Knowledge was the main independent predictor of clinical performance in responding to a virtual deteriorating patient R 2  = 0.090, F (7, 352) = 4.962, p  < 0.001. Discussion: The use of web-based technology allows simulation activities to be accessible to a large number of participants and completion rates indicate that 'Net Generation' nursing students were highly engaged with this mode of learning. Conclusion: The web-based e-simulation program FIRST2ACTTM effectively enhanced knowledge, virtual clinical performance, and self-assessed knowledge, skills, confidence, and competence in final-year nursing students. Highlights: E-simulation allows large numbers of students the opportunity to enhance knowledge and clinical performance. E-simulation as a mode of learning can result in high levels of engagement of 'Net Generation' students. E-simulation can enhance clinical knowledge and knowledge is an independent predictor of clinical performance.